Self-Control of Children Aged 3-4 Years: Predictor Effects of Gentle Parenting and Parents Coping Skills - Muthmainah; Dody Hartanto (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Not all children are able to control themselves well. Parenting is important, but there are still many parents who do not parent properly and have not become good role models. This study aimed to determine: (1) the influence of gentle parenting on self-control of children; (2) the effect of parent coping skill on self-control of children; and (3) the influence of gentle parenting and parent coping skill on self-control of children. This type of research was expost facto. The population of this research was children aged 3-4 years. The sample was 129 children, with incidental sampling technique. Data collection used questionnaires and interviews with parents. The data analysis used multiple linear regression analysis with SPSS. The results showed that: (1) gentle parenting had an effect on self-control of children; (2) the parent coping skill had an effect on the self-control of children; (3) gentle parenting and parent coping skill together affects self-control of children.